2009
DOI: 10.1016/j.biopsych.2008.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Study of White Matter Fiber Tracts in Pediatric Bipolar Disorder and Attention-Deficit/Hyperactivity Disorder

Abstract: Objective-To investigate microstructure of white matter fiber tracts in pediatric bipolar disorder (PBD) and attention deficit hyperactivity disorder (ADHD).Methods-A diffusion tensor imaging (DTI) study was conducted at 3 Tesla on age and IQ-matched children and adolescents with PBD (n=13), ADHD (n=13), and healthy controls (HC) (n=15). Three DTI parameters, fractional anisotropy (FA), apparent diffusion coefficient (ADC), and regional fiber coherence index (r-FCI), were examined in eight fiber tracts: Anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
169
3
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(194 citation statements)
references
References 63 publications
20
169
3
2
Order By: Relevance
“…Lower corticospinal tract and superior longitudinal fasciculus FA (Hamilton et al, 2008) similarly suggested disruption of motor and attention networks in ADHD children, whereas the study by Silk et al (2008) indicated that fronto-striatal and fronto-parietal circuitry abnormalities exist in children with ADHD. Finally, pediatric samples showed decreased FA in the anterior corona radiata and abnormalities across multiple white matter tracts in ADHD, including the cingulum bundle, the superior and inferior longitudinal fasciculi, and internal capsule (Pavuluri et al, 2009). Together, the data argue that white matter abnormalities are associated with ADHD.…”
Section: Selected Adhd Imaging Datamentioning
confidence: 95%
“…Lower corticospinal tract and superior longitudinal fasciculus FA (Hamilton et al, 2008) similarly suggested disruption of motor and attention networks in ADHD children, whereas the study by Silk et al (2008) indicated that fronto-striatal and fronto-parietal circuitry abnormalities exist in children with ADHD. Finally, pediatric samples showed decreased FA in the anterior corona radiata and abnormalities across multiple white matter tracts in ADHD, including the cingulum bundle, the superior and inferior longitudinal fasciculi, and internal capsule (Pavuluri et al, 2009). Together, the data argue that white matter abnormalities are associated with ADHD.…”
Section: Selected Adhd Imaging Datamentioning
confidence: 95%
“…Overall, the few previous DTI studies reported reduced fractional anisotropy and increased radial diffusion in the frontal and prefrontal lobes, internal capsule, corpus callosum and uncinate fasciculus of patients with bipolar disorder. [18][19][20][21][22][23][24] Tract-based spatial statistics (TBSS) is a recently introduced advanced analysis technique that projects all individual DTI parameters onto a group average white matter skeleton, reducing potential spatial misregistrations. 25 Only 2 TBSS studies were performed in young patients with bipolar disorder, showing a reduction in fractional anisotropy, notably in the corpus callosum and fornix 22 as well as in the right uncinate fasciculus.…”
Section: Introductionmentioning
confidence: 99%
“…Although development of self-regulation in children is the result of a dynamic interaction between maturation and learning, we have scarce knowledge about the role played by structural brain characteristics in this process. Recent reports indicate that adjustment problems in childhood psychopathology are related to structural brain characteristics (9)(10)(11)(12)(13), but the brain basis for development of self-regulation in normal children is less well-understood. Thus, the purpose of the present paper was to use multimodal neuroimaging to map the structural brain characteristics related to self-regulation and cognitive control in a large sample of 735 children between 4 and 21 y of age.…”
mentioning
confidence: 99%